Chương I - Căn bậc hai. Căn bậc ba

Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Mai Kawakami

Tính:

1)\(\dfrac{1}{\sqrt{3}-2}\) - \(\dfrac{1}{\sqrt{3}+2}\)

2) \(\dfrac{2}{4-3\sqrt{2}}\) - \(\dfrac{2}{4+3\sqrt{2}}\)

3)\(\sqrt{17-12\sqrt{2}}\) + \(\sqrt{17+12\sqrt{2}}\)

4)\(\sqrt{29-4\sqrt{7}}\)-\(\sqrt{29+4\sqrt{7}}\)

5)\(\sqrt{4+\sqrt{7}}\) - \(\sqrt{4-\sqrt{7}}\)

Phùng Khánh Linh
23 tháng 6 2018 lúc 10:05

\(1.\dfrac{1}{\sqrt{3}-2}-\dfrac{1}{\sqrt{3}+2}=\dfrac{\sqrt{3}+2+2-\sqrt{3}}{3-4}=-4\)\(2.\dfrac{2}{4-3\sqrt{2}}-\dfrac{2}{4+3\sqrt{2}}=\dfrac{8+6\sqrt{2}+6\sqrt{2}-8}{16-18}=\dfrac{-12\sqrt{2}}{2}-6\sqrt{2}\)\(3.\sqrt{17-12\sqrt{2}}+\sqrt{17+12\sqrt{2}}=\sqrt{8-2.2\sqrt{2}.3+9}+\sqrt{8+2.2\sqrt{2}.3+9}=\sqrt{\left(2\sqrt{2}-3\right)^2}+\sqrt{\left(2\sqrt{2}+3\right)^2}=\text{|}2\sqrt{2}-3\text{|}+\text{|}2\sqrt{2}+3\text{|}=4\sqrt{2}\)
\(4.\sqrt{29-4\sqrt{7}}-\sqrt{29+4\sqrt{7}}=\sqrt{28-2.2\sqrt{7}.1+1}-\sqrt{28+2.2\sqrt{7}.1+1}=\sqrt{\left(2\sqrt{7}-1\right)^2}-\sqrt{\left(2\sqrt{7}+1\right)^2}=\text{|}2\sqrt{7}-1\text{|}-\text{|}2\sqrt{7}+1\text{|}=-2\)\(5.\sqrt{4+\sqrt{7}}-\sqrt{4-\sqrt{7}}=\dfrac{\sqrt{8+2\sqrt{7}}-\sqrt{8-2\sqrt{7}}}{\sqrt{2}}=\dfrac{\sqrt{7+2\sqrt{7}.1+1}-\sqrt{7-2\sqrt{7}.1+1}}{\sqrt{2}}=\dfrac{\sqrt{\left(\sqrt{7}+1\right)^2}-\sqrt{\left(\sqrt{7}-1\right)^2}}{\sqrt{2}}=\dfrac{\text{|}\sqrt{7}+1\text{|}-\text{|}\sqrt{7}-1\text{|}}{\sqrt{2}}=\dfrac{2}{\sqrt{2}}=\dfrac{2\sqrt{2}}{2}\)

Trần Minh Hoàng
23 tháng 6 2018 lúc 10:08

1)

\(\dfrac{1}{\sqrt{3}-2}-\dfrac{1}{\sqrt{3}+2}\)

\(=\dfrac{\left(\sqrt{3}+2\right)-\left(\sqrt{3}-2\right)}{\left(\sqrt{3}-2\right)\left(\sqrt{3}+2\right)}\)

\(=\dfrac{4}{\left(\sqrt{3}\right)^2-2^2}\)

\(=\dfrac{4}{3-4}=-4\)


Các câu hỏi tương tự
James Pham
Xem chi tiết
Ngô Khánh Ngọc
Xem chi tiết
Nguyễn Thị Mỹ Hoa
Xem chi tiết
Qúy Công Tử
Xem chi tiết
Trần Hoàng Đạt
Xem chi tiết
Phạm Mai Anh
Xem chi tiết
Qúy Công Tử
Xem chi tiết
Phương Thảo
Xem chi tiết
Ngọc Băng
Xem chi tiết